2007
DOI: 10.1073/pnas.0611650104
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the stringent response is the essential function of the conserved bacterial G protein CgtA in Vibrio cholerae

Abstract: The gene encoding the conserved bacterial G protein CgtA (Obg) is essential for viability in every organism in which it has been studied. CgtA has been reported to be involved in several diverse bacterial functions, including ribosome assembly, DNA repair, sporulation, and morphological development. However, none of these functions have been identified as essential. Here we show that depletion of CgtA in Vibrio cholerae causes global changes in gene expression that are consistent with induction of a classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 46 publications
(63 reference statements)
4
108
2
1
Order By: Relevance
“…The phenotype of the ndx8 mutant is also characterized by a wide range of transcriptional modulations observed in stringent response, e.g. down-regulation of the translational machinery (40,41) and partial activation of the ammonia assimilation (42). In addition, the current study also revealed another transcriptional The intracellular amounts of nucleotides extracted from the wild type (circle) and the ndx8 mutant (square) grown in CS medium were quantified by using HPLC.…”
Section: Discussionmentioning
confidence: 87%
“…The phenotype of the ndx8 mutant is also characterized by a wide range of transcriptional modulations observed in stringent response, e.g. down-regulation of the translational machinery (40,41) and partial activation of the ammonia assimilation (42). In addition, the current study also revealed another transcriptional The intracellular amounts of nucleotides extracted from the wild type (circle) and the ndx8 mutant (square) grown in CS medium were quantified by using HPLC.…”
Section: Discussionmentioning
confidence: 87%
“…The defect occurred at both the permissive and restrictive temperatures, suggesting that this is not the essential function of Obg (Datta et al, 2004). Recent studies show that Vibrio cholera Obg is dispensable in a relA deletion mutant and essentially acts as a repressor of the stringent response by regulating SpoT activity to maintain low ppGpp levels when bacteria grow in nutrient-rich conditions (Raskin et al, 2007). B. subtilis yqeH is classified as an essential gene due to the inability of the IPTG-dependent P spac -yqeH mutant to grow on LB or PAB agar plates in the absence of IPTG.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results in Vibrio cholerae (Raskin et al, 2007) suggest that the Obg orthologue, CgtA, is required to downregulate the stringent response, perhaps by modulation of the ppGpp hydrolase activity of SpoT. Cells depleted for CgtA show gene expression patterns characteristic of constitutive induction of the stringent response.…”
Section: Obg and The Stringent Responsementioning
confidence: 99%